The influence of family characteristics on food parenting practices among parents with school-age children and adolescents: a systematic review - Shahdan, Syazana; Sidek, Suriati (Elsevier, 2025)
Family characteristics can influence parents' implementation of food parenting practices. However, with a growing body of research on family characteristics and food parenting practices, a systematic review of the related topic has yet to be found in the current literature. Hence, the study aimed to review existing studies on family characteristics and food parenting practices among parents with school-age children and adolescents. Family characteristics refer to the family background or demographics that involve race/ethnicity, family income, parents' education levels, food security, culture, acculturation, and family structure. The study used Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for the review process. The data was collected from EBSCOhost Discovery, PubMed, and Scopus databases. Forty-five relevant articles were analyzed and summarized, and the findings were presented in three themes, including (1) culture, races/ethnicities, and acculturation, (2) socioeconomic status and food security, and (3) family structure. The results showed that the family characteristics identified in this study can influence the engagement of food parenting practices among parents with school-age children and adolescents. Several issues have been addressed for the advancement of future research, which can lead to better suggestions and implementation of food parenting practices among parents. Therefore, parents can improve their food parenting experiences and enhance their children's health, growth, and development.